A comparative analysis of gender discourse in Islamic feminist literature and the publications of the Turkish Presidency of Religious Affairs - Korumaz, Esra Keskin (My University, 2016)
Feminism as a social movement has been known around the globe since the late 1890s. Although it aimed to express the concerns of every woman in the world and emancipate them through academic discussions and legal adjustments, the Feminist movement has become a target for harsh criticisms in later years since it failed to represent women of different races, ethnicities, classes and religions. Because of this underrepresentation, new groups of feminists have occurred since the 1990s and Islamic feminism is one of them. The main purpose of Islamic feminists is to reinterpret Islamic texts with a female perspective in order to reveal the gender equality given in the Qur’an and Islam. They also argue that it is the patriarchal interpretations or religious institutions that shape the way of thinking on women and gender issues. In Turkey, the Presidency of Religious Affairs can be given as the most prominent example for the religious institutions that have an impact upon a great number of people in terms of religious matters, including women and gender issues. Setting out from these claims, this dissertation takes the perspectives of Islamic feminists as the focal point of the study and aims to analyze the publications of the Presidency of Religious Affairs. Through these analyses, this dissertation strives for comparing the gender discourse of the Presidency of Religious Affairs publications and Muslim feminists so as to find out the similarities and differences between the two. Bearing this goal in mind, this dissertation focuses on popular periodicals, Friday sermons and books published by the Presidency of Religious Affairs and looks for how women and gender issues such as her position in creation, marriage, family, public sphere and law etc. are explained and unfolded in these publications to draw a general conclusion on the institution’s gender discourse.

Feminizm, 1890'lı yılların sonundan itibaren telaffuz edilmeye başlanmış ve önemli bir toplumsal hareket haline gelmiştir. Bu hareket, akademik tartışmalar ve yasal düzenlemeler yoluyla tüm kadınların sorunlarını dile getirmeyi ve onları özgürleştirmeyi amaçlasa da farklı uluslardan, etnik kökenlerden, sınıflardan ve dinlerden gelen kadınları yeterince temsil etmediği düşüncesiyle sonraki yıllarda sert eleştirilerin hedefi olmuştur. Temsil edilmedeki bu yetersizlik sebebiyle yeni feminist gruplar ortaya çıkmıştır ve İslamcı feminizm de bunlardan birisidir. İslamcı feminizmin ana amacı, İslami metinleri kadın bakış açısıyla yeniden yorumlamak ve Kuran'ın ve İslam'ın bizlere verdiği cinsiyet eşitliğini ortaya çıkarmaktır. Bu Müslüman feministler, aynı zamanda kadın ve cinsiyet sorunlarına olan bakış açımızın ataerkil yorumlamalar ve dini kurumlar tarafından şekillendirildiğini de savunur. Türkiye'de ise kadın ve cinsiyet konularını da içeren dini meselelerde pek çok insanı etkileme gücüne sahip dini kurumlar arasında en önemlisi Diyanet İşleri Başkanlığı'dır. Bu iddialardan yola çıkarak, bu tez İslamcı feministlerin bakış açısını çalışmanın odağına koymakta ve Diyanet İşleri Başkanlığı'nın yayınlarını incelemeyi amaçlamaktadır. Bu analizlerle birlikte, Diyanet İşleri Başkanlığı yayınlarının ve Müslüman feministlerin cinsiyet söylemleri karşılaştırılmaktadır. Bu hedefi gerçekleştirmek için, Diyanet İşleri Başkanlığı'nın yayınladığı dergiler, Cuma hutbeleri ve kitaplar üzerine yoğunlaşılarak yaratılış, evlilik, aile, kamusal alan ve hukuk gibi konularda kadının yeri ve rolünün nasıl anlatıldığı incelenmektedir
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2016
Keywords: Feminism; Gender discourse; Gender equality; Islamic feminism; Presidency of Religious Affairs